What are effective treatments for temporomandibular joint (TMJ) syndrome?. Issue 12 (December 2017) - Wenstrup, Susie; Singh, Harpreet; Arora, Sabrina
Abstract : EVIDENCE‐BASED ANSWER : Gabapentin may reduce TMJ pain by about 30% over placebo, while NSAIDs have demonstrated inconsistent effects (SOR: C, low‐quality RCTs). Corticosteroid and sodium hyaluronate injections have similar short‐term short outcomes (although the effect versus placebo is unknown), but sodium hyaluronate may be better at 6 months (SOR: C, systematic review with conflicting lowquality RCTs).